REPORTING TRANSPARENCY AND ACCOUNTABILITY CIREBON CITY BAZNAS FINANCE BASED PSAK 109 (Case Study on the Cirebon City National Amil Zakat Agency) - Iis Setiyani; Nur Eka Setiowati; Alivien Septian Haerisma (Journal of Economic Development and Village Building, 2023)
This research was conducted to find out how the principles of transparency, accountability, and PSAK 109 are applied in financial reporting. This research was conducted using a qualitative descriptive method. The research time is November 2021 to January 2022 at the Cirebon City National Amil Zakat Agency (BAZNAS). The data collection technique was carried out by interviewing two informants, namely the deputy chairman and the secretary. Data analysis techniques in this study used the Miles and Huberman models, namely data reduction, data display, and conclusion/verification. The results of the study show that transparency principles such as open accountability, accessibility, and publication of financial reports have been implemented. Then the principle of accountability has been applied, namely BAZNAS Cirebon City has met standard implementation procedures, there are sanctions set for errors or omissions in implementing activities and there are measurable outputs and outcomes. BAZNAS Cirebon City has also implemented PSAK 109 since 2017, but the report on assets under management has not been presented. This research can benefit the community around the implementation of PSAK 2017.